The Influence of Interpersonal Communication and Service Quality on Library Satisfaction at Universitas Negeri Medan - Afriadi Amin; Abdul Karim Batubara; Muslih Fathurrahman; Hanny Chairany Suyono; Mayranda Adellia; Wilda Afriyani (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan)
Background: This research uses an effective understanding of interpersonal communication and finds out what influences library users to visit the library at Universitas Negeri Medan.